2017
DOI: 10.1121/1.4973691
|View full text |Cite
|
Sign up to set email alerts
|

Porogranular materials composed of elastic Helmholtz resonators for acoustic wave absorption

Abstract: We present a theoretical and experimental study of the acoustic absorption of granular porous media made of non-cohesive piles of spherical shells. These shells are either rigid or elastic, possibly drilled with a neck (Helmholtz resonators), and either porous or impervious. A description is given of acoustic propagation through these media using the effective medium models proposed by Johnson (rigid particles) and Boutin (rigid Helmholtz resonators), which we extend to the configurations studied in this work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…; Electronic mail: benoit.nennig@supmeca.fr is by multi-layering 15,16 . Other alternative solution is to embed periodic inclusions 17,18 or subwavelength resonators [19][20][21][22][23] to create metaporous materials (resonant inclusions embedded in a porous matrix). Thanks to this approach, it is possible to get a total absorption 24 below the quarter wavelength frequency and to widen the absorption in a specified frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…; Electronic mail: benoit.nennig@supmeca.fr is by multi-layering 15,16 . Other alternative solution is to embed periodic inclusions 17,18 or subwavelength resonators [19][20][21][22][23] to create metaporous materials (resonant inclusions embedded in a porous matrix). Thanks to this approach, it is possible to get a total absorption 24 below the quarter wavelength frequency and to widen the absorption in a specified frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…The resonance frequency of the obtained Helmholtz resonator can be shifted down in comparison to the resonance frequency of a rigid resonator. Griffiths et al [23] presented a comparison between absorption measurements and theoretical models of porogranular media made of soft elastomer elastic HRs. It has been demonstrated that the use of a material with a Young's modulus on the order of 1 MPa or less leads to lower the Helmholtz frequency due to the softness of the elastic resonator.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, double porosity materials that use the pressure diffusion effect between the micro and the macro pore networks have been proposed [3,4,5,6]. Another approach is to excite trapped modes between a rigid inclusion and a rigid wall [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of fluid resonators, membranes [19], thin plates [20] and shell resonances [21,6] have also been considered. These elastic resonators usually resonate at lower frequencies than their fluid counterparts, and avoid the boundary layer thickness constraint that can typically limit the Helmholtz resonator neck diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation